Silent night in Algona [videorecording (DVD)] - Perry, D. J., 1970-; Jacobs, Curran; Rader, Bodhi; Nichols, Taylor (BMG Global, 2023)
Silent Night in Algona is based on a true story set in Algona, Iowa, in 1944. The film captures the resilience of a small town during WWII when a young farmer with a debilitating back injury devises an unconventional plan to save the corn harvest using German POWs. However, fear and resentment spark tensions among the people and could stand in the way. Can the true spirit of Christmas and shared humanity emerge and remind us of the relevance and enduring impact of forgiveness and unity? The story inspires how our similarities outweigh our differences, echoing relevance to modern times.